Natural Carriers for siRNA Delivery - Nedra Karunaratne, D.; Jafari, Mousa; Udayana Ranatunga, R.J.K.; Siriwardhana, Asitha (Current Pharmaceutical Design, 2015)
This review is based on carriers of natural origin such as polysaccharides, proteins, and cell derived entities which have been used for delivery of siRNA. To realize the therapeutic potential of a delivery system, the role of the carrier is of utmost importance. Historical aspects of viral vectors, the first carriers of genes are briefly outlined. Chitosan, one of the extensively experimented carriers, alginates and other polysaccharides have shown success in siRNA delivery. Peptides of natural origin and mimics thereof have emerged as another versatile carrier. Exosomes and mini cells of cellular origin are the newest entrants to the area of siRNA delivery and probably the closest one can get to a natural carrier. In many of the carriers, modifications have provided better efficiency in delivery. The salient features of the carriers and their advantages and disadvantages are also reviewed.
Keywords: peptides